The Relationship Between Learning Readiness and Learning Outcomes of Grade II Elementary School Students: Hubungan Antara Kesiapan Belajar Dengan Hasil Belajar Siswa Kelas II Sekolah Dasar - Bagus Warisman; Vevy Liansary (Universitas Muhammadiyah Sidoarjo, 2021)
This research is motivated by the number of students who lack readiness in learning. This happens when students are doing assignments from the teacher, leaving textbooks behind, and learning readiness so that they can hinder the learning process and affect student learning outcomes. The purpose of this study was to determine whether there was a relationship between student learning readiness and student learning outcomes in grade II SD Negeri Kwedenkembar Mojokerto. The research was conducted using quantitative research with the Pearson bivariate correlation research method using a questionnaire instrument and learning outcomes. The results showed that there was no relationship between student learning readiness and student learning outcomes in grade II SD Negeri Kwedenkembar Mojokerto. This is evidenced by the results of data calculations carried out with a significance value of 0.959 or (0.959 > 0.05), and obtained rcount 0.297 which is known to be smaller than rtable which is worth 0.456 with a significance level of 5% or 0.05. Although it does not have much effect, learning readiness still contributes to students' learning motivation.